Methods to Measure MDSC Immune Suppressive Activity In Vitro and In Vivo. (10th October 2018) - Solito, Samantha; Pinton, Laura; De Sanctis, Francesco; Ugel, Stefano; Bronte, Vincenzo; Mandruzzato, Susanna; Marigo, Ilaria
Abstract: This unit presents methods to assess the immunosuppressive properties of immunoregulatory cells of myeloid origin, such as myeloid‐derived suppressor cells (MDSCs), both in vitr o and in vivo in mice, as well as in biological samples from cancer patients. These methods could be adapted to test the impact of different suppressive populations on T cell activation, proliferation, and cytotoxic activity; moreover, they could be useful to assess the influence exerted by genetic modifications, chemical inhibitors, and drugs on immune suppressive pathways © 2018 by John Wiley & Sons, Inc.